2000
DOI: 10.1046/j.1365-2222.2000.00947.x
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of aerobiological pollutants, chemical pollutants and meteorological conditions on asthma admissions and A & E attendances in Derbyshire UK, 1993–96.

Abstract: Rainfall and thunderstorms are important effect modifiers in the relation between grass pollen and measures of acute asthma morbidity. Interactions between ambient levels of aeroallergens and chemical pollutants in the Derby area do not play a major role in determining asthma admissions and A & E attendance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
69
3
3

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(91 citation statements)
references
References 24 publications
9
69
3
3
Order By: Relevance
“…Our previous asthma panel studies did not find confounding of air pollutant associations by outdoor pollen or fungi (1,7,8). Several time-series investigations have found associations between asthma hospital admissions and both outdoor air pollutants (particles, NO 2 , or O 3 ) and pollen or fungi, but none has found any confounding between aeroallergens and these pollutants (54,60,61). In two studies, there was evidence that SO 2 , NO 2 , and O 3 enhanced the effect of grass pollen on asthma admissions (54,60), although there was a negative interaction between O 3 and tree pollen in one of these studies (54).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Our previous asthma panel studies did not find confounding of air pollutant associations by outdoor pollen or fungi (1,7,8). Several time-series investigations have found associations between asthma hospital admissions and both outdoor air pollutants (particles, NO 2 , or O 3 ) and pollen or fungi, but none has found any confounding between aeroallergens and these pollutants (54,60,61). In two studies, there was evidence that SO 2 , NO 2 , and O 3 enhanced the effect of grass pollen on asthma admissions (54,60), although there was a negative interaction between O 3 and tree pollen in one of these studies (54).…”
Section: Discussionmentioning
confidence: 86%
“…Several time-series investigations have found associations between asthma hospital admissions and both outdoor air pollutants (particles, NO 2 , or O 3 ) and pollen or fungi, but none has found any confounding between aeroallergens and these pollutants (54,60,61). In two studies, there was evidence that SO 2 , NO 2 , and O 3 enhanced the effect of grass pollen on asthma admissions (54,60), although there was a negative interaction between O 3 and tree pollen in one of these studies (54). The general inconsistency between epidemiologic and experimental data on the enhancement of allergen-induced respiratory responses by air pollutants may be explained by a lack of temporally resolved data to account for hourly exposures and a lack of spatially resolved data to account for personal exposures to pollutants and aeroallergens.…”
Section: Discussionmentioning
confidence: 99%
“…Harvey 1967;Corden and Millington 1994;Hollins et al 2004). For example, monitoring campaigns for ambient Cladosporium concentrations and also the fungal genus, Ganoderma, have been carried out throughout the country (Sreeramulu 1963;Lewis et al 2000;Hollins et al 2004). Furthermore, related studies have highlighted the significance of Alternaria, in conjunction with other primary biological aerosol particles (PBAP), for the exacerbation of symptoms in asthma sufferers (Langenberg et al 1977;Corden et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…A positive correlation between pollen or spore counts with allergic symptomology has been found in several clinical trials and in epidemiological studies documenting the impact of aeroallergens on symptom scores (Roberts et al 2005;Takasaki et al 2009), drug consumption (Fuhrman et al 2007 and references therein); consultations for allergic rhinitis (Pedersen and Rung Weeke 1984), emergency visits and hospitalizations (Lewis et al 2000;Lierl and Hornung 2003;Tobias et al 2004;references in Fuhrman et al 2007 andin Peden andReed 2010), and mortality (Targonski et al 1995).…”
Section: Policy Frameworkmentioning
confidence: 90%
“…Schappi et al (1997) found that atmospheric birch pollen allergen concentrations are correlated with birch pollen counts, but that light rainfall produced a dramatic increase in birch allergen-loaded respirable particles in the atmosphere. In Derby, UK, pollen levels had an effect on emergency visits for asthma on days of light rainfall, but not on dry days (Lewis et al 2000). An increased incidence of asthma has been observed in connection with large-scale thunderstorms.…”
Section: Physical and Biological Weathermentioning
confidence: 98%